Modulation of Huntington’s Disease in Drosophila - Subhan, Iqra; Siddique, Yasir H. (CNS & Neurological Disorders - Drug Targets, 2021)
Huntington’s disease (HD) is a progressive neurodegenerative disorder which deteriorates the physical and mental abilities of the patients. It is an autosomal dominant disorder and is mainly caused by the expansion of a repeating CAG triplet. A number of animal models ranging from worms, fruit flies, mice and rat, pig, sheep and monkeys are available, which have been helpful in understanding various pathways involved during the progression of the disease. Drosophila is one of the most commonly used model organisms for biomedical science, due to low cost maintenance, short life span and easy implications of genetic tools. The present review provides a brief description of HD and the studies carried out for HD to date, taking Drosophila as a model.
Keywords: modulation